2022
DOI: 10.3390/cells11132057
|View full text |Cite
|
Sign up to set email alerts
|

ANNEXIN A1: Roles in Placenta, Cell Survival, and Nucleus

Abstract: The unbiased approaches of the last decade have enabled the collection of new data on the biology of annexin A1 (ANXA1) in a variety of scientific aspects, creating opportunities for new biomarkers and/or therapeutic purposes. ANXA1 is found in the plasma membrane, cytoplasm, and nucleus, being described at low levels in the nuclear and cytoplasmic compartments of placental cells related to gestational diabetic diseases, and its translocation from the cytoplasm to the nucleus has been associated with a respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 93 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…As previously mentioned, APCs interact with dying cancer cells, and ANXA1 is released from dying cancer cells. It binds to the formyl peptide receptor 1 (FPR1) on APCs [ 53 , 54 ]. In other words, ANXA1 mediates the uptake of tumor antigens for presentation [ 55 ].…”
Section: Immunogenic Cell Death: An Innovative Approach To Cancer The...mentioning
confidence: 99%
“…As previously mentioned, APCs interact with dying cancer cells, and ANXA1 is released from dying cancer cells. It binds to the formyl peptide receptor 1 (FPR1) on APCs [ 53 , 54 ]. In other words, ANXA1 mediates the uptake of tumor antigens for presentation [ 55 ].…”
Section: Immunogenic Cell Death: An Innovative Approach To Cancer The...mentioning
confidence: 99%
“…The functions of annexin A1 (ANXA1) have a key role in protecting cells against DNA damage [32,33]. The study by Moreli and colleagues found that, in ANXA1 knockout mice (AnxA1−/−), the labyrinth zone of the placenta was reduced, and there was increased DNA damage, causing apoptosis in the labyrinthine and junctional layers.…”
mentioning
confidence: 99%